Comparison of Blood Culture Parameters between 2 and 10 mL Aerobic Bottles from Patients with Sepsis - Kim, Seong Chun; Kim, Sunjoo (Annals of clinical microbiology, 2021)
Background: Blood volume is the most important parameter for an optimal blood culture; however, the effect of blood volume on blood culture is not clearly understood from patients with sepsis. Methods: Blood cultures were obtained from 1,049 patients (≥ 15 years old) who visited the emergency department (ED). Two sets of 20 mL each was collected from each patient, 12 mL of which was transferred to 2 and 10 mL FA Plus (aerobic) bottles (bioMérieux, USA) and the remaining into an FN Plus (anaerobic) bottle. Medical records were reviewed to confirm the diagnosis and clinical significance of the blood culture isolates. The positive rate and time-todetection (TTD) were compared between the 2 and 10 mL groups. Results: Among the 2,098 sets collected, 612 sets (29.2%) were excluded due to inadequate (either too much or too little) blood volume. The positive rate of clinically significant pathogens was lower in the 2 mL group (6.1%) than in the 10 mL group (7.5%) (P = 0.003) among the 1,486 sets. However, there was no significant difference in the positive rate (11.0% vs. 12.5%, P = 0.152) and TTD (15.7 hours vs. 14.2 hours, P = 0.299) among the 585 (39.4%) patients with sepsis. Conclusion: The positive rate and TTD were similar between the 2 and 10 mL groups from patients with sepsis who visited the ED, suggesting a high concentration of bacteremia in this group. Therefore, a smaller blood volume should be carefully considered in patients with sepsis in the ED.